GEOGRAPHIC INFORMATION SYSTEM-BASED MODELING AND ANALYSIS FOR SITE SELECTION OF GREEN MUSSEL, Perna viridis, MARICULTURE IN LADA BAY, PANDEGLANG, BANTEN PROVINCE - I Nyoman Radiarta; Hatim Albasri; Achmad Sudradjat (Indonesian Aquaculture Journal, 2011)
Green mussel is one of important species cultured in Lada Bay, Pandeglang. To provide a necessary guidance regarding green mussel mariculture development, finding suitable site is an important step. This study was conducted to identify suitable site for green mussel mariculture development using geographic information system (GIS) based models. Seven important parameters were grouped into two submodels, namely environmental (water temperature, salinity, suspended solid, dissolve oxygen, and bathymetry) and infrastructural (distance to settlement and pond aquaculture). A constraint data was used to exclude the area from suitability maps that cannot be allowed to develop green mussel mariculture, including area of floating net fishing activity and area near electricity station. Analyses of factors and constraints indicated that about 31% of potential area with bottom depth less than 25 m had the most suitable area. This area was shown to have an ideal condition for green mussel mariculture in this study region. This study shows that GIS model is a powerful tool for site selection decision making. The tool can be a valuable tool in solving problems in local, regional, and/or continent areas.